The synthesis of well-defined poly(vinylbenzyl chloride)-grafted nanoparticles via RAFT polymerization - Moraes, John; Ohno, Kohji; Gody, Guillaume; Maschmeyer, Thomas; Perrier, Sébastien (Beilstein Journal of Organic Chemistry, 2013)
We describe the use of one of the most advanced radical polymerization techniques, the reversible addition fragmentation chain transfer (RAFT) process, to produce highly functional core–shell particles based on a silica core and a shell made of functional polymeric chains with very well controlled structure. The versatility of RAFT polymerization is illustrated by the control of the polymerization of vinylbenzyl chloride (VBC), a highly functional monomer, with the aim of designing silica core–poly(VBC) shell nanoparticles. Optimal conditions for the control of VBC polymerization by RAFT are first established, followed by the use of the “grafting from” method to yield polymeric brushes that form a well-defined shell surrounding the silica core. We obtain particles that are monodisperse in size, and we demonstrate that the exceptional control over their dimensions is achieved by careful tailoring the conditions of the radical polymerization.
Keywords: core–shell particles; free radical; grafting; RAFT polymerization; silica